Survival and progeny production of three economically important stored product insect species on hulled Kernza®, dehulled Kernza®, and hard red winter wheat - Ahmad, Fizra (My University, 2024)
A variety of insect pests are responsible for postharvest losses of cereal grains. Stored product insect pests adversely affect grain quality and quantity of stored commodities. The lesser grain borer, Rhyzopertha dominica (Fabricius) (Coleoptera; Bostrichidae); red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae); and rice weevil Sitophilus oryzae (Linnaeus), are among the most common, serious and polyphagous stored product insect pests that feed on a variety of stored grains. Kernza®, Thinopyrum intermedium (Host) Barkworth & D.R. Dewey, is a low-input perennial cool-season intermediate wheatgrass, grown as a dual-purpose crop for high-quality grazing in the winter and for nutritious whole grain in the summer. No data are available on susceptibility of this novel grain crop to stored-product insect pests, although there are anecdotal reports that the grains from this crop are suffering insect related losses in storage. The aim of this study was to evaluate the survival and progeny production of R. dominica, T. castaneum, and S. oryzae on hulled Kernza®, dehulled Kernza®, and hard red winter wheat. Laboratory reared populations of these stored grain insect pests were introduced in all three tested grain types to record moisture contents (%), survival rate (%), progeny production, kernel damage, and weight loss. Separate experiments were performed for each insect species using completely randomized design (CRD), with 35 replications and seven observation times (7, 14, 21, 28, 35, 42, and 56 d) per grain type. The 7 to 28 d observation times determined survival of the three insect species on the grain types, while the 35 to 56 d observations were used to collect data on adult progeny production. In each replication, 25 adults of mixed sexes and ages were exposed to each of the grain types (50 g) in 150 ml round plastic containers under laboratory conditions of 28°C and 65% r.h. Adult survival (%) was assessed at 7, 14, 21, and 28 d post-infestation. Adult progeny production, kernel damage, and weight loss assessments were done on samples after 35, 42, and 56 d post-infestation. The moisture content during the duration of the experiment varied but the variation was marginal, despite some significant differences. The survival of all three insect species was significantly and consistently lower on hulled Kernza® compared to dehulled Kernza® and hard red winter wheat. Progeny production and weight loss results for R. dominica at 35 to 56 d varied with different grain types, but was generally lowest on hulled Kernza®. In T. castaneum experiments, the mean ± SE survival rate 28 d post-infestation period was significantly lower in hulled Kernza® (9.6 ± 2.4%) compared to dehulled Kernza® (100.0%) and hard red winter wheat (99.2 ± 0.8%). Hulled Kernza® exhibited complete suppression of T. castaneum progeny production in 35, 42, and 56 d samples. However, the mean ± SE kernel damage and weight loss percentage due to T. castaneum infestation was significantly lower i.e., 7.9 ± 0.9 and 1.1 ± 0.5, respectively, in hulled Kernza® compared to the other grain types in 56 d samples. The survival percentages of S. oryzae adults in hulled Kernza® decreased from a mean ± SE of 84.8 ± 2.9 at 7 d to 27.2 ± 4.1 at 28 d. Similarly, smaller numbers of adult progenies of S. oryzae were produced in hulled and dehulled Kernza® than that of hard red winter wheat. At 28 d post-infestation, no adult progeny of S. oryzae was recorded in both hulled and dehulled Kernza®, but a mean ± SE of 21.0 ± 5.4 number of adults were recorded in hard red winter wheat. The mean ± SE weight loss percentage resulting from S. oryzae infestation was in the following order after 56 d: hulled Kernza® (2.2 ± 1.1) < dehulled Kernza® (5.5 ± 0.5) < hard red winter wheat (6.5 ± 0.6). In conclusion, hulled Kernza® appears to be an unsuitable commodity for R. dominica, T. castaneum, and S. oryzae survival and progeny production compared to that of dehulled Kernza®. Therefore, storing Kernza® in its hulled form can be a practical approach to curtail postharvest losses and preserve grain quality, with additional studies warranted on further understanding the possible reasons for poor performance of the three species on hulled Kernza®.
Keywords: Perennial grain seed; Kernza®; R. dominica; Host suitability; Kernel damage; Weight loss